Novel electrochemical sensor for the determination of potassium ions based on silver diethyldithiocarbamate as sensor material - Oguz Özbek; Mehmet Alperen Şahin (Resources Chemicals and Materials)
Potassium is one of the macro minerals necessary for the cellular functions, obtained from foods. Excessive amounts of potassium can cause health problems. Determination of potassium in various samples, especially food and drug samples, is an important task. In this study, we developed a new potentiometric sensor selective to potassium ions. The sensor had a detection limit of 8.64 × 10-5 M in the concentration range of 1.0 × 10-1–1.0 × 10-4 M and a near–Nernstian behavior of 49.0 ± 4.32 mV/decade. The sensor exhibited a response time of 10 s, as well as good selectivity, good repeatability, and a wide pH working range (4.0–11.0). The developed sensor was successfully applied to a drug sample and different water samples with very high recoveries (>91.20 %).